2013
DOI: 10.2166/wst.2013.386
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between water quality parameters and the survival of indicator microorganisms – Escherichia coli – in a stormwater wetland

Abstract: Indicator microorganisms - Escherichia coli - in a stormwater wetland controlling non-point source pollution in the Keum River basin was studied and the relationship between water quality parameters and the survival of E. coli was investigated by Pearson correlation analysis based on 16 sets of data collected on dry days. A significant seasonal variation of the density of E. coli was observed in the influent and effluent. A dominant decay of E. coli was found in almost all the wetland components. In the settli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…On the other hand, it has been reported that a greater amount of dissolved oxygen favors the photo-oxidation and disinfection process (Kadlec and Wallace 2009). As in our research, Cheng et al (2013) found a negative correlation between the levels of dissolved oxygen and the density of E. coli; wetland aeration favored the development of E. coli predators and promoted the photooxidative damage. In Daya Bay (China), the presence of bacteria and microalgae were mainly associated with the concentration of nutrients (nitrates, ammonia, and silicates), which are highly impacted by anthropogenic activities, whereas dissolved oxygen showed a lower correlation (Wu et al 2014).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, it has been reported that a greater amount of dissolved oxygen favors the photo-oxidation and disinfection process (Kadlec and Wallace 2009). As in our research, Cheng et al (2013) found a negative correlation between the levels of dissolved oxygen and the density of E. coli; wetland aeration favored the development of E. coli predators and promoted the photooxidative damage. In Daya Bay (China), the presence of bacteria and microalgae were mainly associated with the concentration of nutrients (nitrates, ammonia, and silicates), which are highly impacted by anthropogenic activities, whereas dissolved oxygen showed a lower correlation (Wu et al 2014).…”
Section: Discussionsupporting
confidence: 84%
“…En cuanto al %OD, se ha registrado que una mayor cantidad de oxígeno disuelto favorece la fotooxidación y, consecuentemente, el proceso de desinfección (Kadlec y Wallace 2009). Al igual que en nuestro trabajo, Cheng et al (2013) encontraron una correlación negativa entre los niveles de oxígeno disuelto y la densidad de E. coli; la aireación del humedal favoreció el desarrollo de depredadores de E. coli y promovió el daño fotooxidativo. En la bahía de Daya (China), la presencia de bacterias y microalgas estuvo asociada a la concentración de nutrientes (nitratos, amonio y silicatos), los cuales son altamente impactados por las actividades antropogénicas, mientras que el oxígeno disuelto tuvo una menor correlación (Wu et al 2014).…”
Section: Discussionunclassified
“…A recent study has shown that the rate of E. coli degradation increases significantly with light intensity (Chan et al, 2015). In the rainy season, however, rainwater drainage canals receive a variety of upstream inputs including sewer overflows, non-human street fecal matter, and residential and commercial water run-off high density (Cheng et al, 2013). The concentration of Enterococci decreased during the rainy season due to dilution.…”
Section: Microbiological Characterization Of Watersmentioning
confidence: 99%
“…The impact of seasonality on the microbial and physicochemical quality of aquatic environments has been reported by several other studies (Cheng et al, 2013;Shabalala et al, 2013;Uzoukwu et al, 2004). Most of these studies have reported a decrease in water quality during the rainy seasons compared to the dry season as a result of increased runoff following rainfall events.…”
Section: Seasonal Variations In the Microbial And Physicochemical Parmentioning
confidence: 81%